Leading with kindness how good people consistently get superior results - Baker, William F. 1942- (American Management Association, 2008)
A new definition of "kindness" for business leaders who want to accomplish true organizational greatness.
Includes bibliographical references and index. - Print version record
Keywords: Leadership; Employee motivation; Organizational effectiveness; Kindness; Personnel; Motivation; Efficacité organisationnelle; Bonté; BUSINESS & ECONOMICS; Leadership